Is bridging therapy still required in stroke due to carotid artery terminus occlusions?. (16th November 2017) - Bourcier, Romain; Alexandre, Pierre-Louis; Eugène, François; Delasalle-Guyomarch, Béatrice; Guillon, Benoit; Kerleroux, Basile; Saleme, Suzana; Marnat, Gaultier; Boucebci, Samy; Mirza, Mahmood; Ferré, Jean-Christophe; Papagiannaki, Chrysanthi; et al.
Abstract : Introduction: Studies comparing endovascular stroke treatment using mechanical thrombectomy (MT) with or without prior IV tissue plasminogen activator (tPa) have included only 30% of internal carotid artery terminus occlusions (ICA-O), a known predictor of recanalization failure with IV tPa. Objective: To carry out a retrospective multicenter analysis of prospectively collected data of consecutive patients to investigate the impact of intravenous thrombolysis on ICA-O by comparing patients treated with MT alone or bridging therapy (BT). Material and methods: Patients with ICA-O treated with MT alone or BT were retrospectively examined and compared. Demographic data, vascular risk factors, treatment modalities, complications, technical and clinical outcomes were recorded. A propensity score (PS) analysis was used to compare modified Rankin Scale (mRS) score at 3 months and intracerebral hemorrhage (ICH) between groups. Results: 141 consecutive patients (60% BT/40% MT) were included between January 2014 and June 2016. Baseline characteristics did not differ between the groups. There was no significant difference in the rate of Thrombolysis in Cerebral Infarction 2b/3, distal emboli, and median number of passes between the groups. There was a significant difference between BT and MT groups in the median time between imaging and groin puncture (median 97 min vs 75, p=0.007), the rate of ICH (44% vs 27%, p=0.05), but not for symptomatic ICH (18% vs 13%, p=0.49). With PS, there was a trend towards a higher rate of ICH (OR=2.3, 95% CI 0.9 to 5.9, p=0.09) in the BT group compared with the MT alone group, with no difference in mRS score ≤2 at 3 months (OR=1.6, 95% CI 0.7 to 3.7, p=0.29). Conclusion: There was no significant difference in clinical outcomes between patients receiving bridging therapy versus direct thrombectomy. Bridging therapy delayed time to groin puncture and increased ICH rate.